Preparation of highly efficient p-doped porous camellia shell-based activated carbon and its adsorption of carotenoids in camellia oil - Tian, Run; Liu, Yang; Cao, Danyu; Gai, Lili; Du, Nan; Yin, Jiangyu; Hu, Dongbin; Lu, Haiqin; Li, Wen; Li, Kai (Frontiers in Nutrition, 2022)
The vegetable oil industry is limited by the high cost of the refining process, and the camellia shells are beneficial to the development of the industry as a biomass raw material for camellia oil decolorization. In this study, camellia shell (CS)-based p-doped porous activated carbon (CSHAC) obtained after the pyrolysis of H3PO4-laden CS-hydrochar (CSH) was used for the adsorption of carotenoids in camellia oil. The results showed that the adsorption efficiency of CSHAC for carotenoids was 96.5% compared to 67–87% for commercial decolourizers, and exhibited a fast adsorption rate (20 min). This superior performance of CSHAC in adsorbing carotenoids was attributed to its micro-mesoporous structure, hydrophobicity, and numerous active sites. The results of adsorption isotherms indicated that the adsorption of carotenoids on CSHAC occurred through a multi-layer process. Furthermore, the analysis of adsorption kinetics showed that the adsorption of carotenoids by CSHAC was a complex process involving physical and chemical reactions, and chemisorption was the dominant kinetic mechanism.